Supplementation of Prenatal Vitamin D to Prevent Children’s Stunting: A Literature Review - Sukmawati S; Hermayanti Y; Fadlyana E; Mulyana AM; Nurhakim F; Mediani HS (Dove Medical Press, 2023)
Sukmawati Sukmawati,1,2,* Yanti Hermayanti,2,* Eddy Fadlyana,3,* Aep Maulid Mulyana,4,* Furkon Nurhakim,5,* Henny Suzana Mediani6,* 1Faculty of Medicine, Universitas Padjadjaran, Bandung, 40132, West Java, Indonesia; 2Department of Maternity Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, 40132, West Java, Indonesia; 3Department of Child Health, Faculty of Medicine, Universitas Padjadjaran, Bandung, 40132, West Java, Indonesia; 4Faculty of Nursing, Universitas Padjadjaran, Bandung, 40132, West Java, Indonesia; 5Department of Fundamental Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, 40132, West Java, Indonesia; 6Department of Pediatric Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, 40132, West Java, Indonesia*These authors contributed equally to this workCorrespondence: Henny Suzana Mediani, Department of Pediatric Nursing, Faculty of Nursing, Universitas Padjadjaran, Bandung, 40132, West Java, Indonesia, Tel +62 822-1739-1965, Email henny.mediani@unpad.ac.idBackground: Stunting is a common nutritional problem in children. Many risk factors contributing to stunting are identified in the literature. Vitamin D supplementation during pregnancy is useful for preventing impairment of fetal bone growth in the womb. However, lack of review in exploring supplementation of prenatal vitamin D is related to stunting in children.Purpose: This study aims to identify the effectiveness of prenatal vitamin D supplementation in preventing stunting.Methods: A literature review was conducted using PubMed, CINAHL, ScienceDirect, and Cochrane Library. Inclusion criteria were a randomized controlled trial study, published between 2011- 2023, a full-text article for pregnant women and an independent variable supplement vitamin D to prevent children's stunting. The keywords used in English were "children OR child" AND "pregnant women" AND "preventive stunting" AND "vitamin D". Study quality was assessed using the Joanna Briggs Institute (JBI) appraisal tool.Results: From the results of the study selection of 511 articles, 11 articles met the inclusion and eligibility criteria for study analysis. Four studies indicated that the administration of vitamin D did not influence the length of the neonate's body or the Length for Age Z-Score (LAZ), used as an indicator of stunting. However, seven articles demonstrated that providing vitamin D supplements to pregnant women impacted various aspects of anthropometry, including the length of the neonate's body. Our findings show that the dosage used of vitamin D in pregnancy varied between 1400- 60,000 per week. Overall, results of this study analysis show that the intervention of prenatal vitamin D supplementation has an impact on the prevention of stunting.Conclusion: This literature review highlighted the benefits of maternal vitamin D during pregnancy and for the children's growth. Prenatal vitamin D supplementation is needed to prevent stunting.Keywords: children, pregnant women, stunting prevention, supplementation vitamin D